Pelatihan Teknik Dasar Pengelasan Listrik (SMAW) bagi Para Pencari Kerja dalam Rangka Peningkatan Produktivitas dan Kinerja Ekonomi Keluarga di Lembang (Desa) Patekke, Kecamatan Makale Selatan Kabupaten Tana Toraja - Adrianus S. Girikallo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The duties and functions of a lecturer are to implement the Tri Darma of Higher Education which consists of teaching and education, research and community service. Community service is intended to participate in advancing community welfare and making the nation's life smarter. For this purpose, community empowerment is carried out through training in basic welding techniques to provide skills for people who have dropped out of school and employees who have been laid off by the Company due to being hit by the economic crisis as a consequence of the spread of Covid-19 globally and having a broad impact on various aspects of human life. The basic welding techniques training activity began with a socialization and discussion session together with educational and community leaders in Patekke Village, South Makale District. The results of the discussion are part of an analysis of situations and phenomena in society in general and for former of PT Malea Energy workers in particular. This training activity aims to provide training participants with skills and competencies so that they can work independently to activate and run the economic activities again. Training materials related to Occupational Safety and Health (K3), Industrial Materials, work facilities and equipment, and working drawings. The benefit of training is increasing HR capacity to increase productivity which is expected to improve the family's economic performance.